2022
DOI: 10.1136/bmjopen-2021-055278
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics associated with COVID-19 vaccine uptake among adults aged 50 years and above in England (8 December 2020–17 May 2021): a population-level observational study

Abstract: ObjectiveTo determine characteristics associated with COVID-19 vaccine coverage among individuals aged 50 years and above in England since the beginning of the programme.DesignObservational cross-sectional study assessed by logistic regression and mean prevalence margins.SettingCOVID-19 vaccinations delivered in England from 8 December 2020 to 17 May 2021.Participants30 624 257/61 967 781 (49.4%) and 17 360 045/61 967 781 (28.1%) individuals in England were recorded as vaccinated in the National Immunisation M… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…We found that views towards COVID-19 vaccination were generally similar across ethnic groups between June and October 2020, while larger UK quantitative studies conducted within the first year after vaccine rollout demonstrated lower uptake in certain ethnic minority groups, and there were sometimes further inequalities by age, gender, religion, area deprivation, disability status, English language proficiency, socioeconomic position and educational attainment 21–24. Surveillance data demonstrate that COVID-19 vaccination rates in the UK and Israel were lowest among certain ethnic minority groups 25 26.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…We found that views towards COVID-19 vaccination were generally similar across ethnic groups between June and October 2020, while larger UK quantitative studies conducted within the first year after vaccine rollout demonstrated lower uptake in certain ethnic minority groups, and there were sometimes further inequalities by age, gender, religion, area deprivation, disability status, English language proficiency, socioeconomic position and educational attainment 21–24. Surveillance data demonstrate that COVID-19 vaccination rates in the UK and Israel were lowest among certain ethnic minority groups 25 26.…”
Section: Discussionmentioning
confidence: 78%
“…Attitudes, intentions and uptake We found that views towards COVID-19 vaccination were generally similar across ethnic groups between June and October 2020, while larger UK quantitative studies conducted within the first year after vaccine rollout demonstrated lower uptake in certain ethnic minority groups, and there were sometimes further inequalities by age, gender, religion, area deprivation, disability status, English language proficiency, socioeconomic position and educational attainment. [21][22][23][24] Surveillance data demonstrate that COVID-19 vaccination rates in the UK and Israel were lowest among certain ethnic minority groups. 25 26 For UK healthcare workers between December 2020 and February 2021, studies found that some ethnic minority groups were more likely to be COVID-19 vaccine hesitant in comparison with white British groups, 12 and that COVID-19 vaccine uptake was lower among some ethnic minority groups compared with white people.…”
Section: Comparison With Existing Literaturementioning
confidence: 99%
“…People with a fragile health might be more inclined to get vaccinated, and also have a higher risk of death from other causes than COVID-19 (Malesza, M., & Bozym, M., 2021). However, frail health can be associated with lower socio-economic status, which is also associated with poor access to health care and lower vaccine uptake (Perry, M., 2021;Tessier et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Vaccine uptake was found to be lowest in some of the communities for whom COVID-19 has the biggest risk, including the Pakistani, Black Caribbean, Black African and Bangladeshi communities, undocumented migrants, and studies have found a strong negative association between socioeconomic deprivation and the rate of declining COVID-19 vaccinations. 11-15 Conversely, higher vaccine acceptance was associated with being White British, older and more educated. 14 Since the COVID-19 vaccines were first rolled out there have been serious concerns about widening health inequalities as a result of uneven uptake and there is emerging evidence to suggest that is the case.…”
Section: Introductionmentioning
confidence: 99%